Maderas de la Formación Piedra Pintada (Jurásico Temprano),provincia de Neuquén, Argentina - Gnaedinger, Silvia Cristina (2006)
Two gymnosperm woods from the Early Jurassic Piedra Pintada Formation at the Cerro Mesa locality, Neuquén province, Argentina, are described. Previous knowledge of the paleoflora is based on leaf impressions. The following taxa are recognized: Araucarioxylon termieri (Attims) Gnaedinger nov. comb. (Order Coniferales, Family Araucariaceae) and a new species, Prototaxoxylon pintadense (Order Taxales). With this contribution, the presence of the Family Araucariaceae is confirmed and the Order Taxales is also added to the assemblage